Computational modeling of AGO-mediated molecular inhibition of ARF6 by miR-145 - Jeremias Ivan; Rizky Nurdiansyah; Arli Aditya Parikesit (Universitas Gadjah Mada, 2020)
Inhibition of ADP-ribosylation factor 6 messenger RNA (ARF6 mRNA) by microRNA-145 (miR-145), mediated by Argonaute (AGO) protein, has been found to play essential roles in several types of cancer and cellular processes. This study aimed to model the molecular interaction between miR-145 and ARF6 mRNA with AGO protein. The sequences of miR-145 and the 3’ untranslated region (UTR) of ARF6 mRNA were retrieved from miRTarBase, followed by miRNA target-site and structure predictions were done using RNAhybrid, RNAfold, and simRNAweb, respectively. The interaction between the miRNA-mRNA duplex and AGO was further assessed via molecular docking, interaction analysis, and dynamics, using PatchDock Server, PLIP, and VMD/NAMD, respectively. The models between miR-145, predicted target site of ARF6 mRNA, and AGO protein returned stable thermodynamic variables with negative free energy. Specifically, the RNA duplex had an energy of -19.80 kcal/mol, while the docking had -84.58 atomic contact energy supported by 70 hydrogen bonds and 14 hydrophobic interactions. However, the stability of the RMSD plot was still unclear due to limited computational resources. Nevertheless, these results computationally confirm favorable interaction of the three molecules, which can be utilized for further transcriptomics-based drugs or treatments.